Globalization and the Margins
XIII, 215 p.
Keywords: Globalization has become one of the dominant ideas of recent times. However, is the debate on globalization as global as it ought to be? In this book Grant and Rennie Short have brought together prominent experts in the field to consider how globalization affects marginalized countries and groups. A variety of case studies provide a unique assessment of the issue of globalization and offer a new look at the relationship between the global and the local.